MANAJEMEN KOMUNIKASI DALAM PROSES PERENCANAAN MEMBANGUN DESTINASI BARU AGROWISATA LEBAH MADU TRIGONA HARAPAN KELUARGA - Arighi Dewantara; I Wayan Suadnya; Yulanda Trisula Sidarta Yohanes; Dian Lestari Miharja (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2022)
This study aims to find out how the communication management carried out by the Harapan Keluarga in the planning process of building an agro-tourism destination in Montong Singgan Village. This study used the descriptive qualitative method. In collecting data the researchers used interview, observation, and documentation techniques. The subjects in this study were members of the Harapan Keluarga group while the object in this study was communication management in developing agro-tourism which contained four stages according to George R Terry's theory in Wibowo and Priansa (2017), namely the planning, organizing, execution process. leadership (acting), and controlling (controlling). The results of this study indicate that there are communication management activities carried out by the Harapan Keluarga group in the planning process of agro-tourism development in Montong Singgan Hamlet. The communication management is carried out through the planning stage which is contained in the 5-year work program. This plan becomes a guideline for the Harapan Keluarga group in building this organization, then the organizing stage is carried out, namely in the aspect of human resource management where the position of members in this organization is placed according to their respective competencies. Then the actuanting stage in this group lies in the activities that have been carried out, such as making agro-tourism support facilities, implementing work programs, and so on. Then the controlling stage is carried out by monitoring and evaluating each work program, group members and group development. Thus, the Harapan Keluarga group cannot be separated from communication management in carrying out the entire series in the agrotourism development planning process in Montong Singgan Hamlet, Salut Village. Keywords: Communication Organization, Harapan Keluarga, Trigona Honey.